Synthesis of Combined Position Regulator - N. N. Mikheev; E. P. Ratkevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The synthesis of a positioning system using a combined position regulator is given in the paper. The paper describes a technique of calculation and forming an input /output position regulator characteristic.A special simple unit for an automatic adjustment and diagnostics of the position regulator with a variable structure is proposed in the paper. This unit practically solves a problem pertaining to complexity and labour-consuming of combined position regulator adjustment.